The Effect of Common Knowledge Construction Model-based Teaching on the Cognitive and Psychomotor Learning of 7th Grade Students - Barış Özden; Nilgün Yenice (Journal of Science Learning, 2020)
This study aimed to investigate the effect of science teaching, based on the Common Knowledge Construction Model (CKCM), on cognitive and psychomotor learning in 7th-grade students. The study group consisted of 29 students from two public schools affiliated with the Ministry of National Education in the 2018-2019 academic year. The study was carried out following a semi-experimental pre-test post-test control group research design. The data were collected with a “Scientific Inquiry Skills Test,” and a “Psychomotor Skills Rubric” (PSR) developed by the researchers. The PSR was used to evaluate the practice exam results of both groups. Data were analyzed with a standard statistics package. It was determined that the scientific inquiry skills post-test scores of the experimental group (X=15.87) were higher than the control group (X=10.92). The difference was observed to be significant. Also, a comparison of the total post-test PSR scores showed a statistically significant difference between the experimental (X=15.44) and control groups (X=13.30).